(untitled) (Revista de Turismo: Patrimônios, Territórios descoloniais e Trabalho, 2023)
The Sempre-Vivas National Park (PNSV) was created in 2002, located in the Serra do Espinhaço, partially covering the following municipalities: Diamantina, Bocaiúva, Buenópolis e Olhos Dágua, in the region of Transespinhaço Trail. The structuring of this section of this trail that passes within the PNSV connecting Inhaí to Curimataí is considered one of the priority needs in the Consultative Council of the Park (CONVIVAS), and was the basis for defining the main objective of this research in partnership with the Tourism Program of the UFVJM, to identify and analyse the offer of tourist attractions in Inhaí, Curimataí and São João da Chapada districts, around the PNSV. As a descriptive research, it includes data collection via bibliographical and documentary research, and field work. A total of 112 attractions were inventoried, divided into natural and cultural attractions, and scheduled events, showing significant tourist potential of the districts. In such a way, the project objectives were encompassed, insofar as the compiled data may assist management bodies and the communities involved in defining local development strategies.